2011
DOI: 10.1007/s10584-011-0257-8
|View full text |Cite
|
Sign up to set email alerts
|

Are homeowners willing to adapt to and mitigate the effects of climate change?

Abstract: The need to adapt to climate change impacts, whilst simultaneously limiting greenhouse gas emissions, requires that the government's efforts are joined by public action. In England and Wales, housing contributes significantly to the emissions and many properties are at risk of flooding. This paper investigates the preparedness of homeowners in England and Wales to make changes to their homes in response to the predicted effects of climate change. A telephone survey of 961 homeowners investigated their interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
116
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(130 citation statements)
references
References 24 publications
10
116
2
2
Order By: Relevance
“…Strong reliance on public authorities may weaken individual motivation to take action but it may make it more likely that the target population will take information provided seriously. There is strong agreement with the view that risk communication is a means of increasing preparedness (Botzen et al, 2009a;Höppner et al, 2012) and previous studies provide insights into the factors that can influence mitigation behaviour, but findings are often ambiguous, and so general conclusions about the effect of risk communication on hazard preparedness cannot yet be drawn. Clarification is required on the extent to which risk awareness and other influences such as knowledge, emotions, or personal experience influence an individual's decision to take protective actions or not.…”
Section: Relevant Findings and Open Research Questions On Risk Preparsupporting
confidence: 72%
See 2 more Smart Citations
“…Strong reliance on public authorities may weaken individual motivation to take action but it may make it more likely that the target population will take information provided seriously. There is strong agreement with the view that risk communication is a means of increasing preparedness (Botzen et al, 2009a;Höppner et al, 2012) and previous studies provide insights into the factors that can influence mitigation behaviour, but findings are often ambiguous, and so general conclusions about the effect of risk communication on hazard preparedness cannot yet be drawn. Clarification is required on the extent to which risk awareness and other influences such as knowledge, emotions, or personal experience influence an individual's decision to take protective actions or not.…”
Section: Relevant Findings and Open Research Questions On Risk Preparsupporting
confidence: 72%
“…Most studies on risk awareness have shown that survey participants are seldom concerned about natural hazards, and their level of preparedness appears to be correspondingly low (Botzen et al, 2009a;Bubeck et al, 2013;Birkholz et al, 2014;Terpstra et al, 2009;Siegrist and Gutscher, 2006;Siegrist, 2013;Thieken et al, 2007;Wachinger et al, 2013;Wagner, 2007). This supports the assumption that there is a relationship between risk awareness and mitigation behaviour.…”
Section: Relevant Findings and Open Research Questions On Risk Preparmentioning
confidence: 69%
See 1 more Smart Citation
“…Some studies have found a minor contribution of risk perception (Bubeck et al 2013, Koerth et al 2013) while others observe a strong link between increased risk perception and increased uptake of measures (Miceli et al 2008, Bichard and Kazmierczak 2012, Osberghaus 2015. Due to the different formulation of risk it is challenging to compare the results across studies.…”
Section: Threat Appraisalmentioning
confidence: 99%
“…Yet practical experience suggests that households do not necessarily implement adaptation measures in order to increase their resilience to flooding (Kunreuther 1996, Peek and Mileti 2002, Bichard and Kazmierczak 2012. Research addressing household decision-making on flood prevention provides limited insights into the communication of flood risk (Dawson et al 2011, Meyer et al 2012, Kellens et al 2013.…”
Section: Introductionmentioning
confidence: 99%